The TNFSF Members APRIL and BAFF and Their Receptors TACI, BCMA, and BAFFR in Oncology, With a Special Focus in Breast Cancer - Kampa, Marilena; Notas, George; Stathopoulos, Efstathios N.; Tsapis, Andreas; Castanas, Elias (Frontiers in Oncology, 2020)
Tumor necrosis factor (TNF) superfamily consists of 19 ligands and 29 receptors and is related to multiple cellular events from proliferation and differentiation to apoptosis and tumor reduction. In this review, we overview the whole system, and we focus on A proliferation-inducing ligand (APRIL, TNFSF13) and B cell-activating factor (BAFF, TNFSF13B) and their receptors transmembrane activator and Ca2+ modulator (CAML) interactor (TACI, TNFRSF13B), B cell maturation antigen (BCMA, TNFRSF17), and BAFF receptor (BAFFR, TNFRSF13C). We explore their role in cancer and novel biological therapies introduced for multiple myeloma and further focus on breast cancer, in which the modulation of this system seems to be of potential interest, as a novel therapeutic target. Finally, we discuss some precautions which should be taken into consideration, while targeting the APRIL–BAFF system.